Mayors and Corruption in Spain: Same Rules, Different Outcomes. Issue 3 (3rd July 2018) - Parrado, Salvador; Dahlström, Carl; Lapuente, Víctor
ABSTRACT: In Spain, there has been widespread corruption in the area of public procurement at the local level, although corrupt practices have not affected all municipalities to the same extent. By comparing two municipalities with 'clean' and 'rotten' corruption records, this article shows that relatively independent bureaucrats—so-called trustees—can act as a check to prevent political moral hazard. Yet, in order to transform their de jure supervisory powers into de facto powers, the trustees must be supported by merit-based human resources policy, rules and standard operating procedures, transparency and independent watchdogs.